Measuring logarithmic signal converter for magnetic tracking systems - Holyaka, Roman; Marusenkova, Tetyana; Fedasyuk, Dmytro (Видавництво Львівської політехніки, 2020)
The work deals with the problem of signal conversion in magnetic tracking systems. Magnetic tracking systems are a novel development trend of navigation sensors within the concepts of the Internet of Things and virtual and augmented reality. In contrast to optical tracking systems, magnetic ones do not suffer from occlusions. In comparison with tracking systems built upon inertial sensors, they are not susceptible to bias drift and provide better accuracy. Magnetic tracking technology is based on calculating the position of objects upon the dynamic measurement of the reference magnetic field vectors. The reference magnetic fields are formed by arrays of actuator coils in the low-frequency electromagnetic radiation spectrum. Those who implement a magnetic tracking system have to ensure noise-immune measurements of signals coming from sensor coils in a wide dynamic measurement range. The range changes from microvolts for distances of several meters in couples “actuator-sensor” to hundreds of millivolts in the case if the distances in “actuator-sensor” couples reduce to several centimeters. Thus, one requires signal converters able to provide highly noise-immune measurements in a dynamic measurement range covering six orders of magnitude. The work presents the results of development, simulation, and investigation into a signal converter for magnetic tracking systems, whose novelty consists in combining the methods of logarithmic amplification and synchronous demodulation of the output signals of the sensor coils. The main nodes of the developed signal converter are a control unit, a logarithmic amplifier, a synchronous demodulator, a low-pass filter, an actuator driver and an analog-to-digital converter. Voltage logarithm compression has been performed upon volt-ampere characteristics of semiconductor p-n junctions. The synchronous demodulator provides a high level of selection of the useful signal out of electromagnetic noise. The results presented in this paper are part of our complex research work related to the development of the Magnetic Tracking System Integrated Development Environment (MTS-IDE). The latter is being developed by a team of scholars within different projects and is aimed at enhancing the efficacy of parametric optimization and synthesizing firmware of embedded systems implementing integrated magnetic tracking sensors. Simulation and experiments have shown that the dynamic range of noise-immune signal measurement using the developed converter covers six orders of magnitude, from 1E-6 V to 1 V. Investigation into functionality were conducted by oscillograph methods. The characteristics of the proposed solution were measured by the above-mentioned MTS-IDE. The obtained results are of key importance for further improvement of magnetic tracking systems, particularly, for their noise-immune measurement volume expansion.
Keywords: Spatial Navigation; Magnetic Tracking; Virtual Reality Devices; Analog Front End; Signal Compression; Logarithmic Converter